Left ventricular and atrial function indexes derived from new echocardiographic techniques are independent prognostic predictors in Chagas Disease - Saraiva, Roberto Magalhães (2017)
O documento encontra-se publicado na revista Circulation, v. 136, suppl. 1, p. A14472, Nov. 14 2017.